2021
DOI: 10.3390/nu13062051
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and Barriers of Zinc Fortification; Experience from 10 Low- and Middle-Income Countries with Mandatory Large-Scale Food Fortification

Abstract: Adequate zinc nutrition is important for child growth, neurodevelopment, immune function, and normal pregnancy outcomes. Seventeen percent of the global population is estimated to be at risk for inadequate zinc intake. However, zinc is not included in the fortification standards of several low- and middle-income countries with mandatory fortification programs, despite data suggesting a zinc deficiency public health problem. To guide policy decisions, we investigated the factors enabling and impeding the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Zinc in high levels and has easily absorbed properties is zinc derived from animal food ingredients. The zinc content of vegetable origin generally binds to oxalates, tannins, and phytates (Tarini et al, 2021) In this study, it was found that 57 people, or 89.1% of third-trimester pregnant women had low zinc intake. The reason for this is thought to be related to the type of food consumed.…”
Section: Discussion a Correlation Between Zinc Intake With Hemoglobin...mentioning
confidence: 73%
“…Zinc in high levels and has easily absorbed properties is zinc derived from animal food ingredients. The zinc content of vegetable origin generally binds to oxalates, tannins, and phytates (Tarini et al, 2021) In this study, it was found that 57 people, or 89.1% of third-trimester pregnant women had low zinc intake. The reason for this is thought to be related to the type of food consumed.…”
Section: Discussion a Correlation Between Zinc Intake With Hemoglobin...mentioning
confidence: 73%
“…Biofortification is the method of increasing the nutrient levels in plants through agricultural, agronomic, T A B L E 2 Summary of enablers and barriers to mandatory food fortification with zinc based on the information from key informants of 10 low-and middle-income countries (Tarini et al, 2021)…”
Section: Biofortificationmentioning
confidence: 99%
“…A recent report from Tarini et al (2021) has established the enabling and impeding factors that impact the inclusion of Zn in the fortification of wheat or maize flour in 10 low‐middle‐income countries (Table 2). For this survey, the authors have chosen six countries (Guatemala, Cameroon, Haiti, Malawi, Indonesia, and Togo) where Zn is present in their fortification standard, and five countries (Guatemala, Mali, Burkina Faso, Philippines, and Cote d'Ivoire) where Zn is not present in standard; in that Guatemala was classified in both the groups owing to their policy of Zn fortification for only maize flour and not for wheat flour.…”
Section: Challenges To Overcome To Meet Current Needsmentioning
confidence: 99%
“…Based on this evidence, the recently updated 2022 WHO wheat flour fortification guidelines include the conditional recommendation to fortify wheat flour with zinc as a public health strategy to improve serum/plasma zinc status (World Health Organization, 2022 ). However, of the 40 LMICs for which zinc deficiency is a public health problem, only 17 include zinc in their mandatory fortification standards (Global Fortification Data Exchange, 2022 ; Tarini et al, 2021 ; K. R. Wessells, personal communication, December 1, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, in accordance with the regional West African Economic and Monetary Union (UEMOA) fortification standard that was subsequently made mandatory in all eight member countries, Burkina Faso implemented legislation mandating the fortification of domestically processed and imported wheat flour with iron and folic acid (Global Fortification Data Exchange, 2022 ; Grant et al, 2018 ). However, despite the estimated high burden of zinc deficiency in the country, zinc was not included in the fortification standard because, at the time the regional standard was developed, there was considered to be a lack of evidence of the efficacy and effectiveness of zinc fortification (Tarini et al, 2021 ). As such, and because wheat flour is already required to be fortified with iron and folic acid, revising the wheat flour fortification standard in Burkina Faso to also include zinc may be a relatively straightforward and low‐cost strategy to increase dietary zinc intakes.…”
Section: Introductionmentioning
confidence: 99%